Towards a better understanding of custodian farmers and their roles: insights from a case study in Cachilaya, Bolivia. - Bioversity International; Gruberg, H.; Fundación para la Promoción e Investigación de Productos Andinos; Meldrum, G.; Padulosi, S.; Rojas, W.; Pinto, M.; Crane, Todd A. (Bioversity International, 2013)
This publication is the result of a research collaboration between Bioversity International and the Fundación para la Promoción e Investigación de Productos Andinos (PROINPA). It deals with issues regarding on-farm conservation of agrobiodiversity, which is a poorly addressed field of research in spite of its pivotal role in the maintenance of global crop diversity. Strategic actors in on-farm conservation are those farmers who, for various reasons, distinguish themselves from others by their contribution to conserving crop diversity. We call them ‘custodian famers’, even though the terminology may not be suitable to all social contexts. Understanding who these custodian farmers are, their presence over the territory, the types of crops they maintain, why and how, as well as gaining insights on the cultural, social and economic drivers behind their efforts is, for scientists, a very important step in devising effective on-farm conservation strategies and this booklet is a contribution in that direction. The open-ended interviews and participant observation methodologies provided in this study are helpful in guiding future methodological approaches and advancing our understanding of how the roles of custodian farmers can be better recognized, harnessed and supported by society. This work has been carried out in the framework of a major global UN Project supported by IFAD and the European Commission, which is focusing on the development of innovative participatory approaches for the conservation of neglected and underutilized species (NUS) on farm.